EXPERT EVIDENCE: DEFINING NEW APPROACH TO THE ADVERSARIAL METHOD IN THE COMMON LAW SYSTEM' - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
This paper is based on library research on the use of expert evidence in the common law system which is conducted at the Law School, the University of Melbourne. Australia. Related to fragility of expert witnesses in an adversarial system. this paper examines whether the use of expert evidence in the common law system promotes objectivity and impartiality. The research shows that the method used in the common law system creates opporÂ¬tunities for the expert to be an advocate for the pare: Moreover, the system allows lawyers to have excessive control over the expert. In order to overcome these weaknesses, this paper offers substantial modification by transplanting a civil law approach to expert evidence into the common law This is in order to better deal with the problems, which may arise in comÂ¬mon law expert evidence. Keywords: Expert evidence, the Common Law System, the Civil Law System